Simultaneous Acute Cardio-Cerebral Infarction: A Rare Case Report Experience in Type C Hospital in Indonesia - Andriani, Nurlita Asri; Mangkoesoebroto, Arjatya Pramadita; Chairina Yuliandita, Rizkia; Pramudyo, Bayu Hendro (Indonesian Basic and Experimental Health Sciences, 2025)
Background: The simultaneous occurrence of ST-elevation myocardial infarction (STEMI) and acute ischemic stroke (AIS) was described as Cardio-Cerebral Infarction. Consequently, we aimed to provide an overview of the available treatment option for patients in type c hospital in order to guide the similar cases. Case Description: A 50-year-old man came to the emergency room complaining of chest pain for two hours before. The patient had a history of hypertension and an active smoker. The patient had a left hemiparesis. The patient's electrocardiogram showed ST segment elevation in leads V3 and V4. A non-contrast head CT-scan showed infarct in the right occipital region. Echocardiogram showed regional wall motion abnormality. The patient was admitted to the hospital, administered DAPT, statin, anticoagulant and discharged after relief of symptoms. Intravenous alteplase followed by primary PCI is the gold standard therapy. However, due to limitation, anticoagulants were chosen and showed clinical improvements. Conclusion: In summary, the goal for treat CCI is to achieve more efficacy therapy while minimising the risk of bleeding. Despite the limitations, patient outcome was good.